Silencing of circRNA.2837 Plays a Protective Role in Sciatic Nerve Injury by Sponging the miR-34 Family via Regulating Neuronal Autophagy - Zhi-bin Zhou; Yu-long Niu; Gao-xiang Huang; Jia-jia Lu; Aimin Chen; Lei Zhu (Elsevier, 2018)
Circular RNAs (circRNAs) represent a class of non-coding RNAs that are involved in transcriptional and posttranscriptional gene expression regulation and associated with different kinds of human diseases. However, the characterization and function of circular RNAs in peripheral nerve injuries remain elusive. Here, we established a rat sciatic nerve injury model and identified at least 4,942 distinct circular RNA candidates and a series of circular RNAs that were differentially expressed in injured nerve tissues compared with matched normal tissues. We characterized one frequently downregulated circular RNA, circRNA.2837, and further investigated its function in sciatic nerve injury. We found that circRNA.2837 regulated autophagy in neurons in vitro and in vivo, and downregulation of circRNA.2837 alleviated sciatic nerve injury via inducing autophagy in vivo. Mechanistically, knockdown of circRNA.2837 may protect neurons against neurological injury by acting as a sponge for members of miR-34 family. Our findings suggested that differentially expressed circular RNAs were involved in the pathogenesis of sciatic nerve injury, and circular RNAs exerted regulatory functions in sciatic nerve injury and might be used as potential targets in sciatic nerve injury therapy. Keywords: circular RNAs, sciatic nerve injury, microRNA, autophagy